Development of a regional transport policy support system for rural planning agencies in developing world - Talpur, M.A.H. (Elsevier Ltd, 2014)
Socioeconomic imbalances and rural poverty are the main rationales of urbanization in developing countries. These problems are the resultant of transport inaccessibility in scattered destitute sub regions. There could be many reasons responsible for inaccessibility, however; this study focuses the issues of rural planning agencies from data absence and its proper management. The aim of this research is to develop a regional transport policy support system. The master plan's data were utilized to develop this tool for rural planning agencies. The research's end product can be helpful in the timely execution of transport policies for the inaccessible rural population of the developing world. Â© 2014 The Authors. Published by Elsevier Ltd.